The philosophy of social injustice for all Indonesian laborers set forth in Job Creation Law - Sunaryo, Sidik (Legality : Jurnal Ilmiah Hukum, 2023)
Working is not only for the sake of earning money, nor is it for the sake of fitting professional rationality. It goes beyond what it appears to be; it represents observances of God. That is, occupations should be seen from a wider perspective implying that it also considers spiritual, immaterial, and material dimensions. The spiritual scope represents the responsibility of humans to their God; the material scope is understood as working for a family, society, the state, and the nation. An occupation carries the spiritual value that represents the social behavior of bearing the responsibility for a job. Mental and social aspects in an occupation carry another meaning of social justice for all Indonesian laborers. Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation, apart from pushing and urging attitude calling for its formulation and pragmatic needs that remain problematic in the eye of society in general, needs testing and reviewing fundamentally from the perspective of social justice principle for all Indonesian laborers. This study is focused on the analysis of the substance of Government Regulation in Lieu of law concerning Job Creation seen from the perspective of social justice for all the workers concerned. This study employs philosophical, conceptual, and statutory approaches to delve into the typical principle of justice in Government Regulation in Lieu of Law concerning Job Creation.